PENGARUH DEBT TO EQUITY RASIO DAN LOAN TO DEPOSIT RASIO TERHADAP RETURN PADA PERUSAHAAN PERBANKAN DI BURSA EFEK INDONESIA - Saputri, Marlinda; Sartika, Dewi (Komunitas Manajemen Kompetitif, 2023)
The aim of this research is to determine the influence of the debt to equity ratio and loan to deposit ratio on returns or what is often also called the stock rate of return. The research population used in this research is banking companies listed on the Indonesia Stock Exchange (BEI). The sample used used a purposive sampling method with the criteria of a banking company that published complete financial reports during the research period, and had a positive equity share. The data used is secondary data obtained from financial reports and obtained from the Indonesian Capital Market of Directory. The statistical test carried out was a normality test with the results of all data having normal distribution, heteroscedasticity and multicollinearity. Hypothesis testing is carried out using quantitative analysis methods through multiple regression models and t-statistical tests. Based on the results of data processing, it can be seen that the Debt to Equity Ratio (DER) and Loan to Deposit Ratio (LDR) do not have a significant effect on stock returns